Analysis of Heat Dissipation and Preheating Module for Vehicle Lithium Iron Phosphate Battery - Shuwen Zhou; Yuemin Zhao; Shangyuan Gao (Energies, 2021)
The ambient temperature has a great influence on the discharge and charging performance of a lithium battery, which may cause thermal runaway of the battery pack in extreme cases. In terms of the poor cooling effect caused by only using the cooling bottom plate for liquid cooling and the fact that the battery pack needs to be preheated before it can be used normally, a new cooling structure design was carried out, and a variety of cooling schemes and preheating schemes were proposed for analysis and comparison. The Star ccm+ simulation software was used to analyze and study their liquid cooling performance and preheating performance under different conditions. The best cooling scheme and preheating scheme were obtained by comparing the results of the simulation analysis. The simulation results show that the cooling performance of the cooling scheme using two vertical cooling plates and one cooling bottom plate is the best, and the preheating performance is best when the preheating liquid is used with a certain temperature flow through the preheating pipe of the battery pack for a period of time, and then the battery pack is discharged until the battery pack temperature reaches the working temperature range. The research results have reference value for the control of the ambient temperature of a vehicle lithium iron phosphate battery.